Prenatal chromosomal microarray testing of fetuses with ultrasound structural anomalies: A prospective cohort study of over 1000 consecutive cases. (22nd August 2019) - Chong, Hsu P.; Hamilton, Susan; Mone, Fionnuala; Cheung, Ka Wang; Togneri, Fiona S.; Morris, Rachel K.; Quinlan‐Jones, Elizabeth; Williams, Denise; Allen, Stephanie; McMullan, Dominic J.; Kilby, Mark D.
Abstract: Objective: Evaluate the diagnostic yield of prenatal submicroscopic chromosome anomalies using prenatal array comparative genomic hybridisation (aCGH). Method: Prospective cohort study conducted between March 2013 and June 2017 including fetuses where an elevated nuchal translucency (NT) or structural anomaly was identified on ultrasound and common aneuploidy testing was negative. aCGH was performed using an 8‐plex oligonucleotide platform with a genome wide backbone resolution of greater than 200 kb and interpretation in line with American College of Medical Genetics guidance. Results: One thousand one hundred twenty‐nine fetuses were included; 371 fetuses with an increased NT (32.9%) and 758 with a structural anomaly (67.1%). The rate of pathogenic copy number variants (CNVs) and variant of uncertain significance (VUS) was 5.9% (n = 22) and 0.5% (n = 2) in the elevated NT group and 7.3% (n = 55) and 0.8% (n = 6) in the mid‐trimester anomaly group. No pathogenic CNVs were identified in fetuses with an NT less than 4.0 mm. Multisystem and cardiac anomalies had the greatest yield of pathogenic CNV with a 22q11.2 microdeletion present in 40% (12/30). Conclusion: Prenatal aCGH is a useful diagnostic tool in the investigation of fetuses with a significantly elevated NT or structural anomaly. With time and experience, rates of pathogenic CNVs have increased, and VUS have reduced, supporting the prenatal application of increasingly high resolution aCGH platforms. Abstract : What is already known about this topic? Chromosome Microarray Analysis (CMA) provides an additional genetic diagnostic yield (sub‐microscopic deletions/rearrangements) of 3% to 5% over and above standard testing strategies in fetuses with structural anomalies. What does this study add? This study assesses the clinical utility of CMA in the current day and demonstrates that with time and experience the diagnostic yield for fetal structural anomalies has doubled with significantly lower rates of variants of uncertain significance (0.6%).